THE THEORITICAL FEASIBILITY OF A MAKE A MATCH STUDENTS WORKSHEET OF MEMBRANE TRANSPORT FOR 2nd SENIOR-HIGH-SCHOOL STUDENTS - YUNITA TRIANA DEVI (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
Most teachers often use teaching method that doesn’t cause enough activity of the student. The students are not motivated and not understanding the abstract materials such as membrane transport. The purpose of this research is to produce a “make a match” student worksheet of the membrane transport material, which is feasibility to the applied in teaching learning process of the high school students. This worksheet was developed using 4-D models from Thiagarajan. The results showed that this student worksheet is included in good to excellent category. Keywords: student worksheet, ‘make a match’, membrane transport